Management of Hemoglobin Disorders During the COVID-19 Pandemic - Chowdhury, Sanjana Fatema; Anwar, Saeed (Frontiers in Medicine, 2020)
The coronavirus disease 2019 (COVID-19) is an emerging infectious disease that has become a global public health concern after being first reported in China and has subsequently spread worldwide. It causes mild to severe respiratory illness with some flu-like symptoms. The causal virus behind this disease, SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), conceivably attacks the receptors of the respiratory system of the human body but has no strict evidence of attacking the blood cells yet. However, patients with hemoglobin disorders (e.g., sickle cell anemia, thalassemia) are vulnerable to this global health situation due to their clinical complications. Such patients are generally more prone to viral and bacterial infections, which can worsen their physical condition. Some of these patients present immunocompromised conditions, e.g., splenectomized or transplantation dependent patients. Therefore, they should follow some preventive steps such as shielding as well as the general guidelines for the COVID-19 pandemic. Transfusion dependent patients require regular monitoring for iron overload, and iron chelation therapy may be stopped by the physician depending on the situation. This article reviews the management strategies and provides some crucial recommendations for people in the corner with hemoglobin disorders.